Cell wall modification by the xyloglucan endotransglucosylase/hydrolase XTH19 influences freezing tolerance after cold and sub‐zero acclimation. (2nd December 2020) - Takahashi, Daisuke; Johnson, Kim L.; Hao, Pengfei; Tuong, Tan; Erban, Alexander; Sampathkumar, Arun; Bacic, Antony; Livingston, David P.; Kopka, Joachim; Kuroha, Takeshi; Yokoyama, Ryusuke; Nishitani, Kazuhiko; et al.
Abstract: Freezing triggers extracellular ice formation leading to cell dehydration and deformation during a freeze–thaw cycle. Many plant species increase their freezing tolerance during exposure to low, non‐freezing temperatures, a process termed cold acclimation. In addition, exposure to mild freezing temperatures after cold acclimation evokes a further increase in freezing tolerance (sub‐zero acclimation). Previous transcriptome and proteome analyses indicate that cell wall remodelling may be particularly important for sub‐zero acclimation. In the present study, we used a combination of immunohistochemical, chemical and spectroscopic analyses to characterize the cell walls of Arabidopsis thaliana and characterized a mutant in the XTH19 gene, encoding a xyloglucan endotransglucosylase/hydrolase (XTH). The mutant showed reduced freezing tolerance after both cold and sub‐zero acclimation, compared to the Col‐0 wild type, which was associated with differences in cell wall composition and structure. Most strikingly, immunohistochemistry in combination with 3D reconstruction of centres of rosette indicated that epitopes of the xyloglucan‐specific antibody LM25 were highly abundant in the vasculature of Col‐0 plants after sub‐zero acclimation but absent in the XTH19 mutant. Taken together, our data shed new light on the potential roles of cell wall remodelling for the increased freezing tolerance observed after low temperature acclimation. Abstract : xth19 mutant had reduced freezing tolerance after cold or sub‐zero acclimation. Microscopic and biochemical characterization of the cell wall indicated altered xyloglucan deposition in xth19 after sub‐zero acclimation showing the importance of cell wall remodelling for increased freezing tolerance.